2009
DOI: 10.2151/jmsj.87.539
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation for the Seasonal Evolution of the Summer Monsoon over the Asian and Western North Pacific Sector in the WCRP CMIP3 Multi-model Experiments

Abstract: Based on the World Climate Research Programme's (WCRP's) Coupled Model Intercomparison Project phase 3 (CMIP3) multi-model dataset, evaluation for the summer monsoon over the Asian and western North Pacific (WNP) sectors is made in terms of reproducibility of the seasonal mean structure. Also investigated is a stepwise eastward progress of convection center from the Indian Ocean toward the WNP in the course of the maturing process of the continental and oceanic monsoons.Most models roughly reproduce seasonal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 33 publications
(48 reference statements)
2
21
0
Order By: Relevance
“…In observations, two stepwise expansions of onset (early June around 5°N, 125°E and middle July around 12.5°N, 135°E) are recognized, whereas the eastward expansions are contiguous rather than stepwise in w-MME. This tendency is similar to our previous study (Inoue and Ueda 2009) based on precipitation data. Figure 3 shows differences of ASM onset dates and their intermodel consistency between 20C3M (1981−99) and SRES-A1B (2081−99) based on w-MME.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In observations, two stepwise expansions of onset (early June around 5°N, 125°E and middle July around 12.5°N, 135°E) are recognized, whereas the eastward expansions are contiguous rather than stepwise in w-MME. This tendency is similar to our previous study (Inoue and Ueda 2009) based on precipitation data. Figure 3 shows differences of ASM onset dates and their intermodel consistency between 20C3M (1981−99) and SRES-A1B (2081−99) based on w-MME.…”
Section: Resultssupporting
confidence: 93%
“…This implies that, in the CGCMs, the monsoon onset over WNP is not directly influenced by the delay of the first transition in mid-May. In many CGCMs, however, convections over the WNP tend to start under a lower in situ SST than that in observations (Inoue and Ueda 2009), suggesting that the reproduction of the seasonal evolution of the WNP monsoon is still fundamental challenging topic in the state-of-theart CGCMs (Wang et al 2005). The delay of the onset over the Bay of Bengal and the South China Sea might be associated with change in large-scale circulations and thermal fields under global warming situations.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition to the changes of the mean-field, it has been reported that the seasonal excursion of rain band will also be modulated under the increase of CO 2 concentration that may affect the duration of the rainy season (e.g., Kitoh and Uchiyama 2006). The projected changes in the late onset and withdrawal of the Baiu rainfall may be associated with the slow establishment of the Asian monsoon and related air-sea interactions (Inoue and Ueda 2009). Despite this fact, our comprehension of the fundamental controlling mechanisms remains deficient.…”
Section: Introductionmentioning
confidence: 99%
“…Ueda et al (2011) used this model to examine the seasonal transition of the Asian monsoon during the LGM. This model is capable of reproducing general features of the Asian summer monsoon including its seasonal transition (Inoue and Ueda 2009). Its atmospheric model is a spectral model with T42 spatial resolution (approximately 2.8°) that uses 30 vertical layers.…”
Section: Idealized Orbital Forcing Experiments In An Aogcmmentioning
confidence: 99%